Perspectives on recovery from older adult trauma survivors living in rural areas. Issue 1 (22nd March 2022) - Duchin, Emma R; Neisinger, Lisa; Reed, May J; Gause, Emma; Sharninghausen, Jody; Pham, Tam
Abstract : Background: Older patients living in rural areas face unique challenges after trauma that may hinder optimal recovery. This study aims to qualitatively assess postdischarge challenges in this vulnerable population. Methods: We conducted remote interviews with older trauma survivors in Washington State previously hospitalized in 2019 and residing in rural areas as determined by rural–urban commuting area code. Participants were identified through our institution's trauma registry and linked with postdischarge data. All eligible participants were contacted. Interview questions focused on needs relating to discharge transition, medical needs, housing, and daily living. Transcribed interviews underwent content analysis to derive a code hierarchy and themes. Results: We conducted 18 interviews out of 83 survivors queried. Compared with non-participants, interviewees had a higher rate of secondary insurance (61% vs 34%), and fewer had an emergency department visit within 1 year (22% vs 34%). Content analysis yielded four major themes: discharge transitions, loss of control, rural insights, and self-efficacy. Most patients felt prepared for discharge and had social support. Regardless of disposition type, most patients needed therapy sessions after discharge. Geography and transportation issues were among the biggest barriers. Most participants were never offered a telemedicine appointment but would have used it if offered. Subthemes of self-efficacy included financial security, leisure, personal outlook, physical and logistical resources, and participants' support systems. Discussion: Older trauma patients from rural areas face unique challenges after discharge. Key strategies to improve patient experience might include more telemedicine appointments and increased awareness of resources in rural communities. Level of evidence: III.